Poor outcome in hypoxic endometrial carcinoma is related to vascular density - Reijnen, Casper; van Weelden, Willem Jan; Arts, Martijn S J P; Peters, Johan P; Rijken, Paul F; van de Vijver, Koen; Santacana, Maria; Bronsert, Peter; Bulten, Johan; Hirschfeld, Marc; Colas, Eva; Gil-Moreno, Antonio; et al. (British journal of cancer, 2019)
BACKGROUND: Identification of endometrial carcinoma (EC) patients at high risk of recurrence is lacking. In this study, the prognostic role of hypoxia and angiogenesis was investigated in EC patients. METHODS: Tumour slides from EC patients were stained by immunofluorescence for carbonic anhydrase IX (CAIX) as hypoxic marker and CD34 for assessment of microvessel density (MVD). CAIX expression was determined in epithelial tumour cells, with a cut-off of 1%. MVD was assessed according to the Weidner method. Correlations with disease-specific survival (DSS), disease-free survival (DFS) and distant disease-free survival (DDFS) were calculated using Kaplan-Meier curves and Cox regression analysis. RESULTS: Sixty-three (16.4%) of 385 ECs showed positive CAIX expression with high vascular density. These ECs had a reduced DSS compared to tumours with either hypoxia or high vascular density (log-rank p = 0.002). Multivariable analysis showed that hypoxic tumours with high vascular density had a reduced DSS (hazard ratio [HR] 3.71, p = 0.002), DDFS (HR 2.68, p = 0.009) and a trend for reduced DFS (HR 1.87, p = 0.054). CONCLUSIONS: This study has shown that adverse outcome in hypoxic ECs is seen in the presence of high vascular density, suggesting an important role of angiogenesis in the metastatic process of hypoxic EC. Differential adjuvant treatment might be indicated for these patients.
Keywords: patologická angiogeneze; hypoxie buňky; Carbonic Anhydrase IX; Adult; Aged; dospělí; senioři; Endometrial Neoplasms; karboanhydrasa IX; senioři nad 80 let; lidé; ženské pohlaví; Cell Hypoxia; Humans; Neovascularization, Pathologic; Aged, 80 and over; Female; lidé středního věku; nádory endometria; Middle Aged